2022
DOI: 10.1007/s12325-022-02344-6
|View full text |Cite
|
Sign up to set email alerts
|

European Physician Survey Characterizing the Clinical Pathway and Treatment Patterns of Patients Post-Myocardial Infarction

Abstract: Introduction:The 2019 European Society of Cardiology and European Atherosclerosis Society (2019 ESC/EAS) guidelines stress the importance of managing low-density lipoprotein cholesterol (LDL-C) after myocardial infarction (MI) to reduce the risk of cardiovascular events. Information on guideline implementation is limited. The aim of this survey was to describe current clinical practice regarding LDL-C management in the first year post-MI across Europe, improving understanding of the role of ESC/EAS guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The heterogenous inclusion of registry patients may account for the discrepancy in findings among Da Vinci cohorts but, overall, the take-home message of inadequate LLT implementation and optimization, as well as low LDL-C target attainment among these registry patients remains the same. A multi-center European study of a physician survey characterizing LLT treatment patterns also showed low levels of therapy intensification, mirroring our results, yet variances in prescribing practices depending upon regions [18].…”
Section: Discussionsupporting
confidence: 86%
“…The heterogenous inclusion of registry patients may account for the discrepancy in findings among Da Vinci cohorts but, overall, the take-home message of inadequate LLT implementation and optimization, as well as low LDL-C target attainment among these registry patients remains the same. A multi-center European study of a physician survey characterizing LLT treatment patterns also showed low levels of therapy intensification, mirroring our results, yet variances in prescribing practices depending upon regions [18].…”
Section: Discussionsupporting
confidence: 86%
“…Even if a patient is not included in a Cardiac Rehabilitation Program after MI, a blood test should be drawn, and a follow-up visit should be scheduled 4 to 6 weeks after hospital discharge, with subsequent LLT optimization if lipidic targets are not reached [ 7 , 15 , 44 ]. However, real-life registries show that the rate of lipid testing after MI is disappointingly low in many countries, and, when performed, it is usually obtained 3 or more months after hospital discharge [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%